The Impact of Foreign Direct Investment on Employment in Indonesia: An Empirical Study of The Manufacturing Sector - Putri Syahiba Kholil (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Foreign Direct Investment (FDI) has become an important driver of industrial development and employment creation in Indonesia’s manufacturing sector. This study examines the development of FDI and its relationship with labor absorption in the manufacturing industry. The research employs a quantitative approach using descriptive statistical analysis based on secondary data obtained from official sources, including government publications and economic reports. The findings indicate that the growth of foreign investment has contributed to industrial expansion through increased production capacity, technological advancement, and stronger integration into global production networks. The analysis also suggests a positive relationship between FDI and employment absorption, as investment inflows create job opportunities directly through manufacturing activities and indirectly through the development of supporting industries and related economic activities. However, the employment impact of FDI is influenced by industrial characteristics, technological intensity, workforce quality, and the strength of domestic industrial linkages. These findings highlight the importance of complementary policies to maximize the economic and employment benefits of foreign investment.